HUBUNGAN FAKTOR SOSIODEMOGRAFI TERHADAP SKOR QUALITY OF LIFE IN EPILEPSY INVENTORY-10 PASIEN EPILEPSI DEWASA DI RSUD DR. SOETOMO - Dwiastri Iris Sarwastuti; Paulus Sugianto; Hanik Badriyah Hidayati; Azimatul Karimah (PERDOSNI, 2021)
Introduction: Several socio-demographic factors, such as age, sex, marital status, level of education, and employment status can determine adult epilepsy patients’ quality of life, which Quality of Life quantitively presents in Epilepsy Inventory-10 (QOLIE-10) score. Aim: This study was to understand the correlation between age, sex, marital status, level of education, and employment status on adult epilepsy patients’ QOLIE-10 score at Soetomo General Hospital. Methods: Analytical observational study using accidental sampling of adult epilepsy patients at Soetomo General Hospital in June 2019-December 2019 was implemented. Several socio-demographic factors were obtained, including age, sex, marital status, level of education, employment status, and their QOLIE-10 score calculation. Correlation analysis against the QOLIE-10 score was carried out, including the Spearman test for socio-demographic factors of age and level of education; and the Mann-Whitney test for socio-demographic factors of gender and marital status, and employment status. Results: Obtained a total of 47 samples with the most common characteristics such as aged 18-25 years (29.8%), male (53.2%), married (57.4%), had the last educational level in senior high school (68.1%), and unemployed (68.1%). Correlation analysis showed an insignificant relationship between age, sex, marital status, recent education, and employment status on the QOLIE-10 score of adult epilepsy patients (p≥0.05). Discussion: Age, sex, marital status, recent education, and employment status did not show a significant relationship to the QOLIE-10 score of adult epilepsy patients. Keywords: epilepsy, QOLIE-10